2015
DOI: 10.1627/jpi.58.20
|View full text |Cite
|
Sign up to set email alerts
|

Noble Metal Phosphides as New Hydrotreating Catalysts: Highly Active Rhodium Phosphide Catalyst

Abstract: Metal phosphide has been widely investigated as a hydrotreating catalyst. The preparation and performance of noble metal phosphide catalyst was examined to develop new phosphide hydrotreating catalysts. The supports affect reducibility of phosphate as a P precursor. Since phosphate does not strongly interact with SiO2 and TiO2 supports, Rh2P was easily formed on these supports. Furthermore, formation of Rh2P enhanced the hydrodesulfurization (HDS) activity of supported Rh _ P catalyst. The type of noble metal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 68 publications
1
19
0
Order By: Relevance
“…New active phases, especiall y nickel phosphide (Ni2P), have received extensive attention . Furthermore, our group [23][24][25][26][27] and Bussell's group [3,28] reported that rhodium phosphide (Rh 2 P) supported on SiO2 exhibits high and stable catal ytic activit y toward the HDS reaction.…”
Section: Introductionmentioning
confidence: 99%
“…New active phases, especiall y nickel phosphide (Ni2P), have received extensive attention . Furthermore, our group [23][24][25][26][27] and Bussell's group [3,28] reported that rhodium phosphide (Rh 2 P) supported on SiO2 exhibits high and stable catal ytic activit y toward the HDS reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The development of the noble metal phosphide catalysts for hydrotreating catalysts shows that Rh 2 P displays the highest activity in the HDS and HDO reactions. The main factors affecting the activity of Rh 2 P are the preparation pathway and precursors, reduction temperature, and support material as shown by the broad investigations by Kanda et al [29][30][31][32][33][34]43,52]. For deoxygenation reactions, cooperative mechanisms of multifunctional or adjacent sites are discussed as a major motive.…”
Section: Discussionmentioning
confidence: 99%
“…Further investigations have shown that Rh 2 P has a higher activity in the HDS of thiophene than all the other PGM phosphides [29]. Due to the higher intrinsic activity of the Rh 2 P catalyst, different publications have focused on the application of Rh 2 P as a catalyst material for hydrotreating reactions [27][28][29][30][31][32][33][34]43,47,52], for the hydrogen evolution reaction [53], and for the hydroformylation [35]. Reviews focusing on the metal phosphides in general and their applications as catalyst materials can be found elsewhere [24][25][26]49,54,55].…”
Section: Rh 2 P As a Prototypic Example For Pgm Phosphides In Hydrotrmentioning
confidence: 99%
See 1 more Smart Citation
“…We reported the effect of reduction temperature and P/Rh ratio on HDS activity of P-added Rh (Rh-P) catalyst. 10,11 Different optimal reduction temperature and P/Rh ratio for HDO activity of Rh-P catalyst would be observed in addition to HDS activity.…”
mentioning
confidence: 99%